The mestizo Augustine : a theologian between two cultures - González, Justo L. (IVP Academic, an imprint of InterVarsity Press, 2016)
"Few thinkers have been as influential as Augustine of Hippo. His writings, such as Confessions and City of God, have left an indelible mark on Western Christianity. He has become so synonymous with Christianity in the West that we easily forget he was a man of two cultures: African and Greco-Roman. The mixture of African Christianity and Greco-Roman rhetoric and philosophy gave his theology and ministry a unique potency in the cultural ferment of the late Roman empire. Augustine experienced what Latino/a theology calls mestizaje, which means being of a mixed background. Cuban American historian and theologian Justo González looks at the life and legacy of Augustine from the perspective of his own Latino heritage and finds in the bishop of Hippo a remarkable resource for the church today. The mestizo Augustine can serve as a lens by which to see afresh not only the history of Christianity but also our own culturally diverse world." --